Computational, geometric, and process perspectives on facial cognition : contexts and challenges - Wenger, Michael J.; Townsend, James T. (Scientific psychology series., 2001)
The subjects covered in this work include: quantitative models of perceiving and remembering faces; the perfect Gestalt; face spaces and other aspects of face perception; predicting similarity ratings to faces using physical descriptions; and the role of category specific processes.